Budget deficits and economic activity in Asia - Gupta, Kanhaya L. (Kanhaya Lal), 1935- (Routledge, 1992)
This book provides extensive empirical evidence on the economic effects of budget deficits in ten Asian countries. It sheds light on a number of important issues relevant for both monetary and fiscal policies in the developing countries.